2022
DOI: 10.1101/2022.05.06.22274683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of a transcriptome-based assay for classifying cancers of unknown primary origin

Abstract: Cancers assume a variety of distinct histologies and may originate from a myriad of sites including solid organs, hematopoietic cells, and connective tissue. Clinical decision making based on consensus guidelines such as NCCN is often predicated on a specific histologic and anatomic diagnosis, supported by clinical features and pathologist interpretation of morphology and immunohistochemical (IHC) staining patterns. However, in patients with nonspecific morphologic and IHC findings—in addition to ambiguous cli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The origin testing platform used in the cases above utilizes a machine learning RNA-based molecular cancer classifier to identify the most likely cancer type from multiple possible cancer types with an accuracy of over 90% [18]. A retrospective study analyzed 289 patients with CUP diagnosis and revealed that cholangiocarcinoma, lung adenocarcinoma, and pancreatic adenocarcinoma were the most common cancer types, as predicted by the origin testing algorithm, and this led to an alteration in therapeutic decision-making in over 80% of the patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…The origin testing platform used in the cases above utilizes a machine learning RNA-based molecular cancer classifier to identify the most likely cancer type from multiple possible cancer types with an accuracy of over 90% [18]. A retrospective study analyzed 289 patients with CUP diagnosis and revealed that cholangiocarcinoma, lung adenocarcinoma, and pancreatic adenocarcinoma were the most common cancer types, as predicted by the origin testing algorithm, and this led to an alteration in therapeutic decision-making in over 80% of the patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…The assay also evaluates transcriptomic alterations from whole-transcriptome RNA sequencing data, including variations in gene expression, altered splicing, and fusions. Sample preparation, DNA sequencing, and RNA sequencing were conducted as described (Leibowitz et al 2022; Michuda et al 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The Tempus TO test is a CAP/CLIA validated molecular diagnostic classifier that uses whole‐exome capture RNA‐seq data as input to provide diagnostic predictions from 68 possible subtypes. The model was trained on 43,726 tumor samples of known origin and has an overall accuracy of 91% based on an independent validation cohort consisting of 9210 tumor samples 11 . For individual patient records, results are reported with one or more predicted diagnoses including the probability that the sample belongs to the given label.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10] The Tempus Tumor Origin (TO) test uses RNA expression data to select from 68 possible histological subtypes and showed a 91% classification accuracy when applied to an independent validation set of samples with known primary. 11 A limited number of studies have evaluated the clinical utility of tissue-of-origin diagnosis via molecular diagnostic classifier in the setting of CUP owing to methodological challenges with studying this population. 12 Several randomized studies have found no significant difference in CUP patient outcomes according to whether they received tissue-specific or empiric therapies, 13,14 while another showed that patients receiving tissue-specific therapies have improved outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation